Prognostic factors of Pasteurella infections: a single-center retrospective cohort study over a 14-year period (2005-2018). (March 2022) - Dernoncourt, Amandine; Lacroix, Mathilde; Duhaut, Pierre; Salle, Valéry; Schmidt, Jean; Batteux, Benjamin; Hamdad, Farida
Highlights: Pasteurellosis must be suspected even in the lack of traumatic sign of animal contact. It appears as a serious disease in vulnerable patients. It may justify intensive care support in case of bacteremia and/or coagulopathies. A genetic susceptibility to develop severe forms of pasteurellosis could be suspected. Abstract: Background: Pasteurella spp . can lead to fatal infections in humans. Objective: To assess prognostic factors of invasive pasteurellosis. Methods: We conducted a single retrospective cohort study of local versus invasive Pasteurella infections from January 1, 2005, to December 31, 2018, in the Amiens-Picardie University Hospital, France. Results: Forty-five (20.9%) invasive pasteurellosis and 22 (10.2%) complicated local infections were reported among a total of 215 Pasteurella infections. The mortality rate among invasive infections was 22.2% (10/ 45) whereas no death was recorded in local infections group. Non–drug-induced prothrombin time test <70% of standard and platelet counts <100, 000/mm 3 were more frequent in non-survivors than in survivors ( p= 0.005 and p= 0.019) in univariate analyses. A history of neoplasia (adjusted OR=13.62, p =0.020), an evidence of bacteremia (adjusted OR=20.68, p =0.025), and hemoglobin level <10 g/dL (adjusted OR=17.80, p =0.028) were identified as poor prognostic factors in multivariate analyses. Conclusion: Invasive pasteurellosis appears as a serious disease in vulnerable patients, particularly if bacteremia and/or coagulopathies occur.